The effects of playing two consecutive matches in the shoulder rotational profiles of elite youth badminton players - Fernandez-Fernandez, J.; Lopez-Valenciano, A.; Del Coso, J.; Gallo-Salazar, C.; Barbado, D.; Sabido-Solana, R.; Ruiz-Perez, I.; Moreno-Perez, V.; Dominguez-Diez, M.; Cabello-Manrique, D. (Physical Therapy in Sport, 2019)
Objective: The aim of the present study was to analyse the effects of playing two badminton matches on the same day on the shoulder profile (i.e., range of motion (ROM) and strength) of young badminton players. Design: Cross-sectional study. Setting: Indoor sports facility. Participants: Thirty-one elite junior badminton players (age 16.6 ± 1.0 years, body mass 63.9 ± 6.1 kg, height 174.8 ± 6.1 cm), including 19 boys and 12 girls. Main outcome measures: Shoulder passive internal rotation (IR) and external rotation (ER) ROM as well as shoulder IR/ER maximal isometric strength were measured before and after a competition including two competitive matches. Results: Significant decreases (p < 0.05) were found in the shoulder ROM (i.e., dominant and nondominant ER ROMs as well as in the dominant and non-dominant total arc of motion [TAM]) in boys, while in girls, significant increases (p < 0.05) were found in the non-dominant ER absolute strength, with significant decreases were found in the non-dominant ER ROM and the non-dominant TAM. Conclusion: Playing two badminton matches on the same day led to gender-specific changes on the shoulder profile (i.e., ROM and strength) of young elite badminton players, with more impact on the shoulder profile of boys compared to girls.